Control model of technological operations of mounting automatic printed circuit boards based on a multiparameter fuzzy classifier - Petrushevskaya, A A (Journal of physics. Conference series, 2019)
In the context of creating digital production, ensuring the concept of continuous support for the product life cycle and the use of big data management systems contributes to the creation of a permanent relationship between all computer-aided design systems implemented at the enterprise. The purpose of the article is to develop a procedure for ensuring the quality of electronic products based on the introduction of intelligent equipment for automatic installation of printed circuit boards based on a multiparameter self-learning fuzzy classifier. To solve the problems of interfacing big data management systems and modern computer-aided design systems, it is proposed to apply the methods of discrete linear or mixed integer programming. Application of logical operations will allow one to simulate the production process in more detail and predict possible disturbances with maximum accuracy.